2017
DOI: 10.1001/jama.2017.0729
|View full text |Cite
|
Sign up to set email alerts
|

Potential Number of Organ Donors After Euthanasia in Belgium

Abstract: Organ donation after euthanasia involves patients whose request to undergo euthanasia has been granted and who voluntarily want to donate their organs after death. It requires patients to undergo euthanasia in the hospital, and organ donation is performed after circulatory death. The practice is controversial and currently only allowed in Belgium and the Netherlands. Even in these countries, it is rarely performed; as of August 2016, 43 patients undergoing euthanasia had donated organs. 1 Organ donation after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 7 publications
0
46
0
1
Order By: Relevance
“…Finally, although some authors have suggested that organ donation after MAiD might have a substantial impact on organ availability, 29,30 the practice of organ donation after MAiD in Canada is still rare. More data about this practice must be collected to determine whether this guidance document is helpful or needs to be updated.…”
Section: Gaps In Knowledgementioning
confidence: 99%
“…Finally, although some authors have suggested that organ donation after MAiD might have a substantial impact on organ availability, 29,30 the practice of organ donation after MAiD in Canada is still rare. More data about this practice must be collected to determine whether this guidance document is helpful or needs to be updated.…”
Section: Gaps In Knowledgementioning
confidence: 99%
“…Lungs, liver, pancreas (islets) and kidneys can be donated and—if applicable—tissues as well. The preliminary transplantation results are promising, and organ donation after euthanasia is is thus clearly of benefit to patients awaiting transplantation 2 34 is beyond the scope of this article.…”
Section: Organ Donation After Euthanasiamentioning
confidence: 99%
“…Finally, there is the question, practical yet morally unacceptable, of the connection between euthanasia and the supply of organs for transplant. A letter to the Journal of the American Medical Association [13] calculates that among the 2023 persons who were officially listed as having died by euthanasia in Belgium in 2015, 204 would have been eligible as organ donors, and then compares this number with that of the patients awaiting organ donation. Any healthcare worker who has worked in intensive care knows the extreme vigilance employed to keep the team taking care of the patient distinct from that which evaluates his/her for brain death as a potential organ donor.…”
Section: How Can the Medical Staff Act Or React To A Request For Euthmentioning
confidence: 99%